PENGARUH ELECTRONIC WORD OF MOUTH, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG KE OWABONG DI PURBALINGGA - Kurnia Widi Setianingsih; Tri Septin Muji Rahayu (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
The purpose of this study is to analyze the variables of electronic word of mouth, quality of service, and promotion of visiting decisions to Owabong visitors in Purbalingga Regency. The sample in the study was tourists who had made a visit to Owabong. Sampling in this study used a purposive sampling approach. Based on the criteria, the sample number of 120 respondents was obtained. The results explained that the variables of electronic word of mouth, quality of service, and promotion simultaneously have a significant effect on visiting decisions. The electronic word of mouth partially had a positive and significant effect on visiting decisions. The quality of service partially affects positively and significantly on visiting decisions. Promotion partially affects positively and insignificantly on visiting decisions. keyword :Electronic Word of Mouth, Quality of Service, Promotion and Visiting Decisions